2015
DOI: 10.1186/s13028-016-0214-7
|View full text |Cite
|
Sign up to set email alerts
|

Progression of experimental chronic Aleutian mink disease virus infection

Abstract: BackgroundAleutian mink disease virus (AMDV) is found world-wide and has a major impact on mink health and welfare by decreasing reproduction and fur quality. In the majority of mink, the infection is subclinical and the diagnosis must be confirmed by serology or polymerase chain reaction (PCR). Increased knowledge based on a systematically description of clinical signs, pathology and histopathology might be a tool to reduce the risk of infection from subclinically infected mink to AMDV free herds. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
0
16
0
2
Order By: Relevance
“…13 In another study, 2 of the 12 wild-type mink inoculated with AMDV showed sprinklers at 24 weeks pi, but none of the other 23 mink tested at 8-and 16-week pi showed sprinklers. 19 The observation that the incidence of sprinklers was not related to antibody titer in the current study but was detected only in the mink inoculated with 10 −4 and higher doses (Table 11), could imply that the duration of infection had the greatest effect on the incidence of sprinklers. The greater proportion of adults with sprinklers than juveniles in the current study, which was parallel with the differences between these two age groups for the prevalence of infection at 20 dpi, is further evidence that the duration of infection was an important factor in the development of sprinklers.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…13 In another study, 2 of the 12 wild-type mink inoculated with AMDV showed sprinklers at 24 weeks pi, but none of the other 23 mink tested at 8-and 16-week pi showed sprinklers. 19 The observation that the incidence of sprinklers was not related to antibody titer in the current study but was detected only in the mink inoculated with 10 −4 and higher doses (Table 11), could imply that the duration of infection had the greatest effect on the incidence of sprinklers. The greater proportion of adults with sprinklers than juveniles in the current study, which was parallel with the differences between these two age groups for the prevalence of infection at 20 dpi, is further evidence that the duration of infection was an important factor in the development of sprinklers.…”
Section: Discussionmentioning
confidence: 51%
“…Furthermore, to establish infection, the amount of virus intake must overwhelm the host's defense mechanism. The immune system of some mink seems to be capable of curtailing the establishment of infection or producing detectable levels of antibodies when exposed to low viral doses, [17][18][19] which is manifested as seronegative mink on chronically infected farms. 9,12,13,20 It is important to know whether the presence of seronegative mink on infected farms was the result of genetic differences or because the level of the virus to which they were exposed was too low.…”
Section: Introductionmentioning
confidence: 99%
“…Reports from 55 sick skunks submitted for histopathologic evaluation were reviewed for lymphocytic and/or plasmacytic infiltration of renal, hepatic, nervous, cardiovascular, pulmonary and endocrine organs, and pneumocyte hyperplasia as reported previously for ADV and SKAV (Alexandersen, ; Allender et al, ; Jensen, Chriel, & Hansen, ; Jensen, Hammer, & Chriel, ; LaDouceur et al, ; Pennick et al, ). Lesions were considered significant unless infiltration was classified in the report as minimal or rare.…”
Section: Methodsmentioning
confidence: 99%
“…The LOESS procedure and segmented regression showed that changes in body weight over time and daily gain were considerably different before and after breeding. Infection with AMDV decreases appetite (Jensen et al 2016), which was manifested as weight loss or slow rate of gain in this experiment. The significantly greater weight loss of the mink fed 1.5% kelp from day 155 (February) to 366 PI (September), which encompassed the pregnancy and lactation periods, was likely the result of significantly larger litter size of this group.…”
Section: Discussionmentioning
confidence: 59%